UMPSA’s visit to MMC explores strategic collaboration in research and innovation - Wallid Wahidi, Hamzah
KUALA LUMPUR, 13 August 2025 – The meeting between the delegation of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and MMC Corporation Berhad (MMC) today is set to explore strategic collaboration in research and innovation that will benefit both parties.